Gender equality and higher education: Challenges to be achieved in the European Union - María Matarranz; Eva Ramírez (Arizona State University, 2018)
In the late 19th century, the first movements in the pursuit of women legal rights were born in Europe, mainly claiming women's rights to work, to vote and to get access to education. The gradual acquisition and generalization of these rights during the twentieth century re-focused the initiatives of gender equality towards new fields, including economics and political representation. During the twenty-first century, despite social progress and thanks to them, the actual level of gender equality in Europe continues to pose a major focus of interest, as demonstrated by the work program of the European Commission for the period 2010-2015 on gender equality. This interest comprises the area of education at a national, international and supranational level, showing a clear development of education policies on equality. Since education is the greatest driver of social change, this trend can be seen as the best representation of the defense of equality between women and men. Thus, it seems appropriate to analyze the education policies on gender equality that have penetrated from international scenarios to supranational and national spaces, such as the European Union and its member countries. After reviewing the policies on gender equality published in the last decades, we use the comparative methodology to study the five least populated states of the European Union: Estonia, Slovenia, Malta, Luxembourg and Cyprus.